Hydatid Cyst Protoscolices Induce Cell Death in WEHI-164 Fibrosarcoma Cells and Inhibit the Proliferation of Baby Hamster Kidney Fibroblasts In Vitro - Hossein Yousofi Darani; Narges Soozangar; Soliman Khorami; Fatomeh Taji; Mortaza Yousofi; Hedayatollah Shirzad (Journal of Parasitology Research)
Both in vitro and in vivo models have demonstrated that some parasites can interfere with tumor cell growth. The present study investigates the anticancer activity of hydatid cyst protoscolices on WEHI-164 fibrosarcoma cells and baby hamster kidney (BHK) fibroblast cells in vitro. Those above two cell types were treated with live hydatid cyst protoscolices or left untreated for control groups. After 48 h, lactate dehydrogenase (LDH) and cell counts were assayed for both treated cells and control groups. Following treatment with hydatid cyst protoscolices, cell proliferation of both cell types was inhibited, and lysis of fibrosarcoma cells increased. Based on these results, it appears that hydatid cyst protoscolices have strong anticancer activity, and additional studies are needed to further clarify the mechanisms of this activity.